A Study on Factors Influencing Resource Leveling and Smoothing on Time Cost Trade-Off - P. Kulanthaivel, V. Mayilsamy, S. Saravana, N. Nandhini (International Journal of Advanced Science and Technology, 2020)
Construction enterprise has been described as the entire industry related to the utilization of human, natural, and financial resources in the conception, design, and production, protection, and demolition of construction and civil engineering works. Construction projects are precise in nature, having their personal difficulties, uncertainties,dangers, posing never-ending questions concerning the resources and fees. The achievement of a mission relies upon the performance with which the assignment management receives the paintings done through using the deliberate resources of guys, substances, equipment, time, and money. Resource leveling and smoothing is very much important to balance the requirements for resources with presented supply and to prevent project delays arising from bad allocation and helps project managers identify and make use of unused bench time. It is also necessary to smooth the resources when you have to optimize the resources, and you cannot extend the schedule. 125 questionnaires are distributed to various engineers through Google forms. Finally, we concluded that there are many factors which affect the resource leveling and smoothing to some extent. Some of those factors are Lack of awareness, Thinking resource leveling as an unnecessary process, Over allocation of resources, Prohibited work breaks lead to stress, Budget Overrun and unnecessary labor charges, Problems while handling multiple projects mostly affect the Resource leveling and smoothing process.